Implementation of the Criminal Prosecution Process at the Tanjung Perak District Attorney’s Office Surabaya - Faria, Milena Miranda; Wahyuni, Silvi Ika Nur; Wahyu Agung, Genzha Nur (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The prosecutor’s office plays an important role in the criminal justice system, particularly in carrying out the prosecution process for criminal cases. This study aims to determine the implementation of the criminal prosecution process at the Tanjung Perak District Attorney’s Office Surabaya. The research method used is a qualitative method with a descriptive approach through observation and documentation of the case administration process in the general crime division. The results show that the prosecution process is carried out through several stages, namely the examination of case files, issuance of P-21, Phase II which includes the transfer of suspects and evidence, preparation of the indictment, and the implementation of court proceedings. In conclusion, the criminal prosecution process at the Tanjung Perak District Attorney’s Office Surabaya has been carried out in accordance with applicable legal procedures.